Evaluation of Photovoltaic Penetration on System Grid with Minimum Loading Approach - Dawam Habibullah; Khin Moe Moe; Syafii Syafii (Andalasian International Journal of Applied Science, Engineering and Technology, 2023)
The Indonesian government has also set a target to increase the contribution of renewable energy in the national energy mix to 23% by 2025 and 31% by 2050. In this paper, an analysis of Maximum PV Capacity was used on the transmission network with a minimum loading approach using the Power Factory15.1 simulation. From the simulation that has been done, it can be seen that the placement of two PV location points gets better results than the placement of one PV location point. This can be seen that the feeder load for PV location point of 74.3%, while for two PV location points of 35.8% which value is still within safe limits, but for two PV location points get better results. PV trip state frequency values obtained for single location point and two PV location points get a result of 2% of 50 Hz which is still within safe limits.